Fruit and vegetable intake in relation to gastric cancer risk: A comprehensive and updated systematic review and dose-response meta-analysis of cohort studies - Naemi Kermanshahi, Mohammad; Safaei, Ehsan; Tutunchi, Helda; Naghshi, Sina; Mobarak, Sara; Asadi, Masoomeh; Sadeghi, Omid (Frontiers in Nutrition, 2023)
Background: Since the release of previous meta-analyses, some studies on the associations between fruit and vegetable intake with gastric cancer risk have been published. Therefore, we aimed to update the previous meta-analyses on these associations by including recently published studies as well as considering the main limitations of those meta-analyses. Methods: A comprehensive search was conducted in online databases including PubMed, Scopus, ISI Web of Science, and Google Scholar to detect relevant prospective cohort studies published up to October 2021. Summary relative risks (RRs) were estimated using a random-effects model. Results: Overall, 17 articles containing 18 prospective studies with a total sample size of 1,527,995 participants, aged between 18 and 90 years, were included in the current meta-analysis. During the follow-up periods ranging between 4.5 and 21 years, 8477 cases of gastric cancer were diagnosed. A higher intake of total fruit (RR: 0.87, 95% confidence interval (CI): 0.80 to 0.94, I2=0%) and total fruit and vegetable (RR: 0.75, 95% CI: 0.61 to 0.93, I2=55.2%) were associated with a lower risk of gastric cancer. For total vegetable intake, a significant inverse association was found among the studies that controlled their analysis for energy intake. Based on the linear dose-response analysis, each 100 g/day increase in total fruit intake (Pooled RR: 0.95, 95% CI: 0.90 to 0.99, I2=49%) and 200 g/day increase in total fruit and vegetable intake (RR: 0.94, 95% CI: 0.88 to 0.99, I2=37.6%) were associated with a 5% and 6% lower risk of gastric cancer, respectively. Conclusion: Fruit and vegetable consumption has a protective association with gastric cancer risk.